Numerical Evaluation of the Effect of Global Equivalence Ratio on Confined Turbulent Non-Premixed Flames - NODA, Susumu; Kapuruge Don Kunkuma Amila SOMARATHNE (Journal of Environment and Engineering, 2013)
The control of nitrogen oxides (NOx) is currently a major issue in designing an effective combustion system because NOx has several detrimental effects on the environment and human health. However, it is difficult to understand NOx formation processes in flames because of complicated interactions between the flow and chemistry. In this study, a partially-stirred-reactor combustion model is implemented in the OpenFOAM CFD tool to model confined turbulent non-premixed propane jet flames, and the NOx emission is evaluated in terms of the global equivalence ratio. The code solves Reynolds-Averaged Navier Stokes equations on an unstructured mesh in a cylindrical coordinate system. The computational predictions of scalar and flow fields in the combustion chamber are extensively compared to experimental measurements, and they show a good agreement. The oxidation and heat-release rates of propane are computationally evaluated, and they are used to verify the scalar fields such as temperature and mole fractions of species. The increase in the global equivalence ratio increases the maximum temperature of the furnace because of the enhancement of reaction rate, and thereby, leads to the enrichment of the NOx emission.